Psikoedukasi Fathering untuk Meningkatkan Keterlibatan dan Kompetensi Ayah dalam Pengasuhan Anak - Mochammad Sa'id; Rakhmaditya Dewi Noorrizki; Mutia Husna Avezahra (I-Com: Indonesian Community Journal, 2024)
Parenting is one of the main factors affecting the child's future psychological development. Nevertheless, many people still overestimate the role of the mother and ignore the importance of the father's role in parenting. Therefore, this community service activity is carried out with the aim of raising the knowledge, awareness, and skills of parenting of the fathers. This activity is packed in the form of psycho-education of fathering for the fathers in the neighborhood of RT 05 Perum Graha Gilang Purnama, Kedungrejo Village, Pakis Sub-District, Malang District. There are three main subjects given in this activity: Concept of Parenting and Its Types, Father's Role in Parenting, and Simulation of Parenting Practice. Based on reflection and evaluation of the activities carried out, it can be concluded that the psycho-education of fathering has successfully improved the knowledge, awareness, and skills of fathers in terms of fathering. The participants realized that their role parenting was very important, and they increasingly understood how to do fathering to their children.